O-148 Does trophectoderm biopsy affect the initial level and rate of increase in serum ß-HCG levels? A comparison of preimplantation genetic testing (PGT) and non-PGT cycles. (30th June 2022) - Hocaoglu, M; Ozer, G; Okten, S.B; Kahraman, S
Abstract: Study question: Does trophectoderm biopsy affect the initial level and rate of increase in ß-HCG levels after single frozen-thawed blastocyst transfer?A comparison of PGT and non-PGT cycles. Summary answer: Initial serum β-hCG concentrations from cycles resulting in a live birth was significantly lower than that for the non-PGT group. What is known already: β-hCG may serve as early predictor of pregnancy outcome and potentially assist in reducing stress related to the uncertainty of outcome in assisted reproductive technologies (ART) treatments and counselling. hCG is produced primarily by differentiated syncytiotrophoblasts. Due to removal of trophectoderm cells, the secretion of β-hCG may be affected. Little, however, is known about the influence of trophectoderm biopsy on serum β-hCG levels in early pregnancy. Therefore, it is important to investigate if the levels and pregnancy outcomes predictive values of β-hCG vary in PGT and non-PGT cycles. Study design, size, duration: This was a single center retrospective cohort study conducted at Assisted Reproductive Technologies and Reproductive Genetics Center, Istanbul Memorial Hospital, Istanbul, Turkey between January 2012-January 2021. A cohort of women with frozen-thawed single blastocysts transfers and having positive serum ß-HCG results on day 9 following ET (≥20 IU/L) were allocated into two groups; PGT group (1777 cycles) and non-PGT group (1874 cycles). Participants/materials, setting, methods: The serum ß-hCG levels on day 9 and 11 after embryo transfer (ET) and the rate of ß-hCG increase were compared between the PGT and non-PGT cycles with respect to biochemical pregnancy loss (BPL), clinical pregnancy loss (CPL), and live birth. The cutoff values of initial β-hCG levels and the rate of ß-hCG increase from day- 9 to day-11 were evaluated for live birth and compared between the two groups. Main results and the role of chance: Initial β-hCG levels were significantly higher in pregnancies resulting in live birth (184.68±99.54 IU/L, p = <0.001) compared to BPL (66.65±55.29 IU/L) and CLP (140.51±88.98 IU/L) in the PGT group. Moreover, initial β-hCG levels were significantly higher in pregnancies resulting in live birth (192.53±97.93 IU/L, p = <0.001) compared to BPL (73.67±58.07 IU/L) and CLP (156.28±98.29 IU/L) in the non-PGT group. In addition, initial serum β-hCG concentrations from cycles resulting in a live birth was 184.68±99.54 IU/L for the PGT group, which was significantly lower than that for the non-PGT group (192.53±97.93 IU/L, p = 0.004). The diagnostic threshold of initial β-hCG levels predicting a live birth was 122.5 IU/L (sensitivity 70.1 %, specificity 60.1 %, PPV 84.7 %, and NPV 38.9 %) and 130.5 IU/L (sensitivity 71.7 %, specificity 61.6 %, PPV 82.2 %, and NPV 46.9 %) in the PGT and non-PGT groups, respectively. The rate of increase of serum β-hCG threshold predicting a live birth for the PGT group was 2.33 (sensitivity 73.8 %, specificity 59.9 %, PPV 85.3 %, and NPV 42 %) and 2.42 (sensitivity 64.6 %, specificity 60.1 %, PPV 80 % and NPV 40.7 %) for the non-PGT group. Limitations, reasons for caution: This is a retrospective analysis. Wider implications of the findings: Initial serum β-hCG values and the rate of β-hCG increase may be useful for predicting pregnancy outcomes in PGT cases undergoing trophectoderm biopsy. Trial registration number: Not applicable